2018
DOI: 10.1002/cnma.201800066
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic and Photonic Effects on Hydrogen Evolution over Chemically Modified Titania Inverse Opals

Abstract: The photonic effects of chemically modified titania inverse opals can be exploited for improving photocatalytic hydrogen production. This work reports the in situ preparation of gold-platinum nanoparticle (NP)-loaded and nitrogenfluorine co-doped titania inverse opal photocatalysts with different photonic band gaps (PBGs). In situ loading of gold and platinum NPs was carried out during the preparation of titania inverse opals by treating the titania precursor with gold chloride and platinum chloride. AuÀPt/NÀF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Recently, plasmonic PCs have been intensively investigated to combine both PBG and LSPR effects together in terms of physical appearances and electronic energies for various applications [104][105][106][107][108][109]. An interesting study has been shown for negative photoresist IO (prepared by SiO 2 opal embedding) deposited with gold, where the dual-colored micropatterns (Figure 3) open the door for possible applications in various fields, including cosmetics, optical filters and coatings [104].…”
Section: Nm-based Pcsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, plasmonic PCs have been intensively investigated to combine both PBG and LSPR effects together in terms of physical appearances and electronic energies for various applications [104][105][106][107][108][109]. An interesting study has been shown for negative photoresist IO (prepared by SiO 2 opal embedding) deposited with gold, where the dual-colored micropatterns (Figure 3) open the door for possible applications in various fields, including cosmetics, optical filters and coatings [104].…”
Section: Nm-based Pcsmentioning
confidence: 99%
“…The fabrication of PCs-based plasmonic photocatalysts is quite challenging process to load/infiltrate plasmonic NPs on/in the PCs without destroying the Bragg's diffraction property of the PCs and to retain the effective LSPR effect of NMs. The photodeposition and thermal methods have been commonly used to deposit plasmonic NPs on IO by using the adequate precursors, such as chloroplatinic acid (H 2 PtCl 6 ) for Pt [112], silver nitrate (AgNO 3 ) for Ag [113], and tetrachloroauric acid (HAuCl 4 ) for Au [106]. NMs have been deposited on TiO 2 IO either before [106] or after [99] its infiltration inside opal structure.…”
Section: Preparation Of Pcs-based Plasmonic Photocatalystsmentioning
confidence: 99%
See 3 more Smart Citations